Community-Acquired Pneumonia in Children: A Multidisciplinary Consensus Review - Donald E Low; James D Kellner; Upton Allen; Francois D Boucher; Thomas Kovesi; John Riesman; Ross Davidson; Joanne M Langley (Canadian Journal of Infectious Diseases)
Community-acquired pneumonia (CAP) is common among children and may have viral, bacterial or, occasionally, other causes. The etiology is complex, with age-related trends, and differs from that in adult CAP, necessitating different management guidelines. There is an absence of current guidelines for the management of pediatric CAP (PCAP) that take into account changing etiologies, antimicrobial-resistance issues and the use of newly licensed antimicrobials. The present review does not provide specific guidelines, but it reviews the literature and presents currrent approaches to the treatment of PCAP. To compile the review, an expert panel was convened to provide a consensus. The review discusses the etiology, diagnosis and antimicrobial treatment of PCAP as well as indications for referral to a hospital emergency department. The goal of the review is to provide those involved with treatment of PCAP in the community setting with information that can be used to make effective treatment choices.